Elemental examination in blood and urine samples of Jordanian children with autism spectrum disorder - Ayat Hussein B. Rashaid; Tasneem Shanayneh; Mazin Alqhazo; Mahmoud Bashtawi (Biomarkers in Neuropsychiatry)
Autism Spectrum disorder (ASD) is one of the psychiatric disorders with unknown etiology, which possibly affects children in the first three years of their life. This case-control study was performed to explore the differences in concentrations of 9 elements: sodium (Na), aluminum (Al), potassium (K), calcium (Ca), vanadium (V), manganese (Mn), cobalt (Co), thorium (Th), and uranium (U) in whole blood and urine specimens of children with ASD, neurotypical children, and their mothers. The study investigates the associations between the elements, sex, and severity of ASD. Methods and Materials: The study rincluded 21 children with ASD and 19 age-sex-matched neurotypical children. Elemental analysis was carried out by inductively coupled plasma-mass spectroscopy (ICP-MS). The behaviors of ASD were assessed using the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM–5) and the Childhood Autism Rating Scale (CARS). The results indicated a significant increase of Al (198 ± 87, p= 0.05) and significant decrease of Ca (50 ± 3, p= 0.007) and Mn (10 ± 1, p= 0.004) in blood sample of ASD compared to the neurotypical group. In the urine sample, a significant decrease level appeared in Ca (41 ± 10, p=0.05) of ASD compared to neurotypical. The maternal samples showed no significant difference between ASD and neurotypical. The main finding of this study could help the specialist to diagnose and relieve symptoms of ASD. Thus, the heavy and trace elements analysis is a biomarker for ASD.